Pengaruh Variabel Ekonomi dan Non Ekonomi tentang Indek Kebanggaan Orang di Indonesia - Sutikno (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
This study aims to measure the influence of economic and non-economic variables on the index of public happiness in Indonesia. The independent variables used in this study include: Economic Growth, Per Capita GRDP, Criminal Level, Unemployment Rate and General Allocation Fund (DAU) with Ordinary Least Square (OLS) analysis analysis techniques. From the calculation results, variables that have a significant influence on the welfare index in Indonesia are per capita GRDP, General Allocation Fund (DAU), Criminal Level, and Education Level. Whereas the insignificant variable in this model is economic growth. The independent variable in the model also has a significant influence of 4.73%. That is, when all the variables in this model move, the happiness index will change by 4.73%.